Predictability of exchange rates with Taylor rule fundamentals: Evidence from inflation-targeting emerging countries - ALBA, Joseph D. (Institutional Knowledge at Singapore Management University, 2015)
We investigate the out-of-sample predictability of U.S. dollar exchange rates with Taylor rule fundamentals in thirteen emerging countries with inflation-targeting monetary policy regimes. We find some evidence of out-of-sample exchange rate predictability for Brazil, Czech Republic, Hungary, Philippines, Thailand, and South Africa. Plots of the coefficients of U.S. inflation and Philippine inflation predict the direction of the U.S. dollar-Philippine peso exchange rates to be opposite to that predicted by the Taylor principle.